Una congregación ocupada de las "cosas trabajosas y humildes". Las hermanas de la caridad en Morelia. Siglos XIX y XX - Vázquez Carmona, Alejandra (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
The congregation of the Sisters of the Charity, also well-known as Daughters of San Vicente of Paúl, they have played an important part in the Mexican society for the services toasted in the area of the health, the education and the social attendance. In particular, the Sisters have been in charge of from the attention to the poorest in situations of shortage, either in the hospitals, houses for sick mental, asylums, orphanages, jails and schools. That is to say that their work has been guided to the altruistic services that benefit the neighbor, as well as in its constant preparation and upgrade of the necessities in the world. In 1844, the congregation of the Sisters of the Charity arrived to Mexico amid wars, armed risings, interventions and guerrillas that razed to great part of the society, mainly to the sectors more desprotegidos from the second half of the XIX century. The work carried out by the Daughters of San Vicente of Paul was recognized by the president Benito Juárez, who excepted them of the law of prohibition of religious orders promulgated in 1861, to be consecrated to the aching" humanity's service; later on the president Dull Sebastian of having Tiled expelled the Sisters of the Charity from the country when rising in 1873 to constitutional range the Organic Laws of Reformation.

La congregación de las Hermanas de la Caridad, también conocidas como Hijas de San Vicente de Paúl, han desempeñado un importante papel en la sociedad mexicana por los servicios brindados en el área de la salud, la educación y la asistencia social. En particular, las Hermanas se han ocupado de la atención a los más pobres en situaciones de escasez, ya sea en los hospitales, casas para enfermos mentales, asilos, orfanatos, cárceles y escuelas. Es decir, que su labor se ha orientado a los servicios altruistas que beneficien al prójimo, así como en su constante preparación y actualización de las necesidades en el mundo. En 1844, la congregación de las Hermanas de la Caridad arribó a México en medio de guerras, levantamientos armados, intervenciones y guerrillas que asolaron a gran parte de la sociedad, sobre todo a los sectores más desprotegidos desde la segunda mitad del siglo XIX. La labor realizada por las Hijas de San Vicente de Paul fue reconocida por el presidente Benito Juárez, quién las exceptuó de la ley de prohibición de órdenes religiosas promulgada en 1861, por “estar consagradas al servicio de la humanidad doliente”; posteriormente el presidente Sebastián Lerdo de Tejada expulsó a las Hermanas de la Caridad del país al elevar en 1873 a rango constitucional las Leyes Orgánicas de Reforma.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2008-0016; Opción en historia de México; Congregación hermanas de la caridad; Morelia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2384